Technological Pedagogical and Content Knowledge (TPACK): The Students’ Perspective on Writing Class: TPACK - Farikah Farikah; Moch. Malik Al Firdaus (Jurnal Studi Guru dan Pembelajaran, 2020)
This study reports the profile of Technological Pedagogical and Content Knowledge (TPACK) of Writing lectures from the students’ perspective. It described the students’ attitudes and opinion on the implementation of Technological Pedagogical and Content Knowledge (TPACK) during joining the teaching-learning activities of writing class. Adopting qualitative descriptive study framework, fifty students participated in fulfilling the questionnaires on the implementation of Technological Pedagogical and Content Knowledge (TPACK). Closed questionnaire was implemented as the research instrument in collecting the data. Closed questionnaire was used to measure 7 (seven) TPACK domains, namely: 1. Technological Knowledge, 2. Pedagogical Knowledge, 3. Content Knowledge, 4. Technological Pedagogical Knowledge, 5. Technological Content Knowledge, 6. Pedagogical Content Knowledge, 7. Technological Pedagogical Content Knowledge. The results show that the ability of lecturers of writing class in applying TPACK is at enough criteria.